1982
DOI: 10.1007/bf00692699
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neurovisceral mannosidosis associated with?-mannosidase deficiency in a family of Persian cats

Abstract: Several kittens in a family of Persian cats had a metabolic storage disease. Clinically the disorder was characterized by hepatomegaly, neurological signs and early death. The microscopic lesions consisted of widespread vacuolation of neurons and glial cells in the central nervous system and in liver cells. Electronmicroscopically the lesions consisted of intracytoplasmic accumulation of membrane-bound "empty" vacuoles. In addition to the storage disease, poor myelination of the cerebral white matter was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 15 publications
6
30
0
Order By: Relevance
“…31 CNS pathology in feline AMD includes cellular swelling, decreased myelin, and astrogliosis. [5][6][7]12 It has been reported that AMD cats imaged at 1.5T have significant decreases in the magnetization transfer ratio (MTR) of white matter compared with normal cats, 12 whereas the MTRs were increased in cats treated with gene therapy, 14 providing evidence that MTR could be used to monitor improvements in myelination associated with therapy. These studies showed that MTR was a useful noninvasive antemortem method to quantify myelin deficiency subsequently confirmed postmortem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 CNS pathology in feline AMD includes cellular swelling, decreased myelin, and astrogliosis. [5][6][7]12 It has been reported that AMD cats imaged at 1.5T have significant decreases in the magnetization transfer ratio (MTR) of white matter compared with normal cats, 12 whereas the MTRs were increased in cats treated with gene therapy, 14 providing evidence that MTR could be used to monitor improvements in myelination associated with therapy. These studies showed that MTR was a useful noninvasive antemortem method to quantify myelin deficiency subsequently confirmed postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…2 Naturally occurring AMD has also been described in cattle, cats, and guinea pigs, and a knockout mouse has been created. [3][4][5][6][7][8][9][10] AMD cats have essentially the same clinical, biochemical, and neuropathologic abnormalities as human patients 11 and have a severe clinical phenotype with grossly obvious neurologic signs, a generally uniform disease course, and death by 6 months without treatment. 12 The feline model has proved to be useful in the evaluation of experimental therapies including bone marrow transplantation and gene therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Feline α-mannosidosis shows similar clinical finding, including multiple skeletal deformities, retarded growth, ataxia, intention tremors and deficiency in the acidic MANB activity (Burditt et al, 1980;Walkley et al, 1981;Vandevelde et al, 1982). In addition, the affected cats share similar phenotypic heterogeneity with the human patients, suggesting that the cats are suitable model system for studying the human disease (Raghavan et al, 1988).…”
Section: Animal Modelsmentioning
confidence: 91%
“…23,24,27 Neuropathological findings include vacuolated neurons, glia, and endothelial cells throughout the brain and spinal cord; Purkinje cell loss; and myelin deficiency of the central and peripheral nervous systems. 27 Feline alpha-mannosidosis Spontaneously occurring AMD has been reported in cats, [28][29][30][31][32][33][34] cattle, [35][36][37][38][39][40][41][42] and guinea pigs, [43][44][45] and a knockout mouse has been created. 46 Interestingly, disease can also be induced by ingestion of the indolizidine alkaloid swainsonine, which is found in locoweed plants.…”
Section: Alpha-mannosidosismentioning
confidence: 99%